DETERMINAN FINANCIAL TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN FOOD AND BEVERAGE DI INDONESIA - SEVIANY; NILA PUSVIKASARI (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
The purpose of this study is to examine the effect of financial ratios such as profitability, asset growth, capital structure, liquidity, and company size on dividend policy. The research objects consist of food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2016–2024 period. The samples used in this study consisted of 27 companies for logistic regression analysis and 9 companies for panel data regression analysis that meet the criteria of the purposive sampling method. The data were analyzed using SPSS software for logistic regression and E-views 13 software for panel data regression as statistical analysis tools. The results of the statistical analysis indicate that profitability, asset growth, capital structure, liquidity, and company size do not have an impact on dividend policy.